The negation of the statement $(p \vee q)^{\wedge}(q \vee(\sim r))$ is
$((\sim p) \vee r) \wedge(\sim q)$
$((\sim p) \vee(\sim q))^{\wedge}(\sim r)$
$((\sim p) \vee(\sim q)) \vee(\sim r)$
$(p \vee r)^{\wedge}(\sim q)$
For any two statements $p$ and $q,$ the negation of the expression $p \vee ( \sim p\, \wedge \,q)$ is
The negation of the statement $(( A \wedge( B \vee C )) \Rightarrow( A \vee B )) \Rightarrow A$ is
$\left( {p \wedge \sim q \wedge \sim r} \right) \vee \left( { \sim p \wedge q \wedge \sim r} \right) \vee \left( { \sim p \wedge \sim q \wedge r} \right)$ is equivalent to-
If the truth value of the Boolean expression $((\mathrm{p} \vee \mathrm{q}) \wedge(\mathrm{q} \rightarrow \mathrm{r}) \wedge(\sim \mathrm{r})) \rightarrow(\mathrm{p} \wedge \mathrm{q}) \quad$ is false then the truth values of the statements $\mathrm{p}, \mathrm{q}, \mathrm{r}$ respectively can be:
Negation of $p \wedge( q \wedge \sim( p \wedge q ))$ is